How safe are our children in vehicles on the road? a Malaysian perspective - Sambasivam, Sivasankar; Karuppiah, Karmegam; Md Tamrin, Shamsul Bahri; Sadeghi, Hassan; Subramanian, Kulanthayan; Zainal Abidin, Emilia; Puvanasvaran, A. P.; Su, Meng Ya (Malaysian Public Health Physicians' Association, 2017)
As Malaysia races towards a developed nation status, children are increasingly being ferried daily in vehicles almost exclusively as the majority of the population are able to afford private transportations. This paper reviews the current safety concerns for children whilst going in vehicles on Malaysian roads and the steps undertaken to address the need to enhance children’s safety whilst going in these vehicles and suggest possible remedial action to counter the possible lack of awareness for children’s safety whilst in these vehicles. This paper focuses on children on motorcycles and private vehicles (cars, vans and multi-purpose vehicle (MPV)) and excludes other form of transport (buses, lorries) as this paper tries to put forth measures that can be undertaken by the children’s parents and guardian to better enhance the safety of their children. A search was undertaken of all the major database of articles. Articles related to children’s safety systems, children related injuries, children related accident data, available laws and legislation were reviewed to present the need for greater awareness of children’s safety while going in vehicles in Malaysia. There are currently already safety legislations, measures, steps and equipments in place in ensuring the safety of children whilst going in vehicles on Malaysian roads. However, enforcement of laws in developing countries are not easy and we have to start at the root of the problem which is the parents and adults who ferry these children in vehicles. There is a pressing need to educate parents and adults alike on the urgent undertaking of child safety whilst in vehicles. Engineering countermeasures and intervention are probably needed to protect these vulnerable users. For vehicles, a device capable of providing some sort of protection to the child whilst riding pillion should be designed and developed. A legislation mandating the use of child seats whilst ensuring the child seats are affordable to the masses.